Integrin-mediated interactions control macrophage polarization in 3D hydrogels - Cha, Byung-Hyun; Shin, Su Ryon; Leijten, Jeroen; Li, Yi-Chen; Singh, Sonali; Liu, Julie C.; Annabi, Nasim; Abdi, Reza; Dokmeci, Mehmet R.; Vrana, Nihal Engin; Ghaemmaghami, Amir M.; Khademhosseini, Ali (Wiley, 2017)
Adverse immune reactions prevent clinical translation of numerous implantable devices and materials. Although inflammation is an essential part of tissue regeneration, chronic inflammation ultimately leads to implant failure. In particular, macrophage polarity steers the microenvironment towards inflammation or wound healing via the induction of M1 and M2 macrophages, respectively. Here, we demonstrated that macrophage polarity within biomaterials can be controlled through integrin mediated interactions between human monocytic THP-1 cells and collagen-derived matrix. Surface marker, gene expression, biochemical and cytokine profiling consistently indicated that THP-1 cells within a biomaterial lacking cell attachment motifs yielded pro-inflammatory M1 macrophages, whereas biomaterials with attachment sites in the presence of IL-4 induced an anti-inflammatory M2 like phenotype and propagated the effect of IL-4 in induction of M2 like macrophages. Importantly, integrin α2β1 played a pivotal role as its inhibition blocked the induction of M2 macrophages. The influence of the microenvironment of the biomaterial over macrophage polarity was further confirmed by its ability to modulate the effect of IL-4 and lipopolysaccharide, which are potent inducers of M2 or M1 phenotypes, respectively. Thus, our study represents a novel, versatile and effective strategy to steer macrophage polarity through integrin mediated three-dimensional (3D) microenvironment for biomaterial-based programming. This development has wide implications for controlling inflammation, angiogenesis, cell proliferation, and tissue regeneration for a myriad of applications including tissue engineered implants, drug delivery vehicles, and implantable devices.